The effect of preventive exercises using the (isometric) method and aids to help develop the strength of the thigh muscles of the first-class referees of the Iraqi Premier League - Flayih , Mustafa; Mahdi , Hamid (Journal of Physical Education, 2023)
The aim of the research is to identify the values of the level of muscular strength of the thighs, as well as to identify the significance of the differences between the pre-tests and the post-tests for the first-class football referees in the Iraqi Premier League. The researchers used the one-group experimental approach for its suitability to the nature of the study problem, and the research sample was from first-class referees in the Iraqi Premier League for the sports season (2022/2023), and their number was (15) referees. They took the comprehensive enumeration method, and special tests were conducted on them in the stadium and the private hall at the Ministry of Youth and Sports Center. After analyzing and discussing the results, the two researchers concluded that there are significant differences between the pre and posttests and in favor of the post tests of the research group because of the preventive exercises in the (isometric) manner and aids to develop the strength and balance of the thigh muscles prepared for this purpose. In this regard, the researchers recommend conducting extensive studies for this group and paying attention to the preventive aspect of referees in order to avoid their exposure to injuries in the thigh muscles, which are among the most common injuries in this group.